The Routledge handbook of child and family social work research : knowledge-building, application, and impact - Fernandez, Elizabeth, 1942- (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This handbook provides an accessible resource for all social work students, educators, practitioners and policy makers to increase their knowledge and understanding of how research into the diversity and impact of child and family social work interventions might underpin and drive policy and practice. Divided into six sections -The Context of Child and Family Social Work Research -Preventive and Reparative Responses to Children and Families -Child Maltreatment: Causes, Consequences, and Responses -Alternate Care as an Approach to Safeguarding Children and Young People -Intervention: Therapeutic Responses to Vulnerable Children, Youth, and Families -Child and Family Social Work in the Global Context and comprised of 52 newly written chapters by experts in the field, it provides a foundational overview of the field of child and family social work, including defining concepts, sentinel historical milestones, and the scope of practice. It also identifies developments in auxiliary fields such as neuroscience, psychology, education, health, poverty, and media By illustrating diverse research endeavours in parenting, maltreatment, prevention, child protection, substitutive interventions including foster care, residential care, adoption, juvenile corrections; elaborates child welfare research methods, measures, and impacts on practice, it analyses evidence-based interventions and policies in early intervention, child protection, child placement, adoption, and advocacy. It will be required reading for anyone working in social work and child protection"--
Keywords: Child welfare; Social service; Family social work; SOCIAL SCIENCE / Human Services; SOCIAL SCIENCE / Children's Studies